Tunable high speed pulse generator for phase change memory (PCM) / Rosalena Irma Alip ...[et al.] - Alip, Rosalena Irma; Tuan Yaakub, Tuan Norjihan; Rasin, Munirah; Zulkafli, Mohamad Fazullah; Harun, Harzul Hazwan (UiTM Press, 2015)
This project presents a model representation of storing data in a Phase Change Memory (PCM) using a high speed pulse generator. PCM is considered to be one of the promising candidate for the next generation memory device. Phase-change material, the chalcogenide alloys will be used to fabricate the memory layer of the PCM. A pulse generator is needed to induce pulses into the memory layer, for the switching process. Conventional pulse generator is quite large in size and it is difficult to control the exact value of pulse that being induced, due to the internal resistance of the connection. To overcome this problem, an integrated tuneable high speed pulse generator is needed. A tunable high speed pulse generator was designed by varying the RC circuit to have adjustable pulse width. The EDA Tools such as Mentor Graphics will be used to design the schematics and layouts. The tunable high speed pulse generator was designed by using 0.13µm technology. Pulse width from the integrated pulse generator ranging from 100µs – 100ns was induced to the PCM in order to give supply to PCM. To monitor the switching process, PCM will be connected to a simple output circuit. When the memory layer is successfully changes into crystalline phase, the LED will be ‘ON’ because of the current flow. When the memory is erased, which is when it changes back to the amorphous phase the LED will be ‘OFF’, since there will be no current flow due to the high resistance of the amorphous phase. As a conclusion, the project present an integrated circuit that helps PCM to switch phases from amorphous phase to crystalline phase or vice versa at high speed, in order to fulfill the demand of a high speed memory.